Analisis Pengaruh Pengungkapan Enviromental, Social, And Governance (ESG), Tingkat Utang, dan Ukuran Dewan Terhadap Kinerja Perusahaan dengan Ukuran Perusahaan sebagai Variabel Moderasi: Studi pada Perusahaan Non-Keuangan yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2022 - Muhammad Faiz Fahreza; Mochammad Chabachib (Diponegoro Journal of Management, 2025)
This study examines the influence of ESG disclosure, debt levels, and board size on ROA in non-financial firms listed on the Indonesia Stock Exchange (2018–2022), using firm size as a moderator. Data from 63 companies were analyzed through multiple linear regression and Moderated Regression Analysis (MRA) in EViews 13. The results show that ESG disclosure and board size positively affect ROA, while debt levels have a negative impact. Furthermore, firm size strengthens both the positive effects of ESG and board governance and the negative effect of debt. The findings suggest that while larger firms benefit more from sustainable practices and governance, they also face greater financial risks from high leverage. The study highlights the need for balanced ESG integration and debt management to optimize financial performance.